Interrelationship among components of lodging and yield in pea (Pisum sativum L.) - Singh, AK; Tyagi, N; Srivastava, CP (Vegetable Science, 2012)
Pea (Pisum sativum L.) is one of the six major pulse crops cultivated globally and is the second highest yielding legume in the world after common bean, Phaseolus vulgaris L. (FAO database, 2010). Pea has been grown as an important source of human food and animal feed for many centuries. Similar to other pulse crops, pea is also prone to different biotic and abiotic stresses causing substantial yield losses. In addition, lodging is also a major constraint in pea production. Lodging usually referred to a condition in which the stems of plants bend at or near the surface of the ground, which could lead to the collapse of the canopy. Lodging enhances the canopy microclimate for fungal disease development, reduces photosynthetic ability of the plants, reduces harvest efficiency and increases harvest cost. For such reasons, lodging can cause upto 74% yield loss in some dry pea cultivars (Amelin and Parakhin 2003). In view of this, concerted efforts are needed to enhance pea productivity by selecting genotypes with high standability and stable yield. The present investigation was undertaken to assess the nature of association among lodging resistance and yield and yield related components in pea.